Selective dorsal rhizotomy in ambulant children with cerebral palsy: an observational cohort study. (July 2019) - Summers, Jennifer; Coker, Bola; Eddy, Saskia; Elstad, Maria; Bunce, Catey; Bourmpaki, Elli; Pennington, Mark; Aquilina, Kristian; Cawker, Stephanie; Edwards, Richard; Goodden, John; Hawes, Sally; et al.
Summary: Background: Selective dorsal rhizotomy (SDR) is an irreversible surgical procedure involving the division of selected sensory nerve roots, followed by intensive physiotherapy. The aim is to improve function and quality of life in children with cerebral palsy and a Gross Motor Function Classification System (GMFCS) level of II or III (walks with or without assistive devices, respectively). We assessed gross motor function before and after SDR and postoperative quality of life in a study commissioned by NHS England. Methods: We did a prospective observational study in five hospitals in England who were commissioned to perform SDR on children aged 3–9 years with spastic diplegic cerebral palsy. The primary outcome was score changes in the 66-item Gross Motor Function Measure (GMFM-66) and seven domains of the Cerebral Palsy Quality of Life Questionnaire ([CP-QoL] social wellbeing and acceptance, feelings about functioning, participation and physical health, emotional wellbeing and self-esteem, access to services, family health, and pain and impact of disability) from before to 24 months after SDR. Findings: From Sept 4, 2014, to March 21, 2016, 137 children underwent SDR. The mean age was 6·0 years (SD 1·8). The mean GMFM-66 score increased after SDR with an annual change of 3·2 units (95% CI 2·9 to 3·5, n=137). Of the seven CP-QoL domains, five showed significant improvements over time: feelings about functioning mean annual change 3·0 units (95% CI 2·0 to 4·0, n=133), participation and physical health 3·9 units (2·5 to 5·3, n=133), emotional wellbeing and self-esteem 1·3 units (0·2 to 2·3, n=133), family health 2·0 units (0·7 to 3·3, n=132), and pain and impact of disability −2·5 units (−3·9 to −1·2, n=133). 17 adverse events were reported in 15 children, of which none were severe and 15 (88%) resolved. Interpretation: SDR improved function and quality of life in the 24 months after surgery in children with cerebral palsy classified as GMFCS levels II and III. On the basis of these findings, an interim national policy decision was made that SDR would be funded for eligible children in England from 2018. Funding: National Institute for Health and Care Excellence, National Institute for Health Research Biomedical Research Centre, NHS England.